Efficacy effects of fecal microbiota transplantation on depressive symptoms: a meta-analysis based on randomized controlled trials - Fu, Jiamin; Zhang, Yuchi; Gao, Jing; Lan, Ming; Zhang, Zhixin; Liang, Ruiting; Zhou, Hongyun; Liu, Shirui; Zhou, Ziyi; Zhao, Jinwan; Yu, Xing; Liu, Yuewen; et al. (Frontiers in Psychiatry, 2026)
BackgroundThe gut microbiota plays a crucial role in the bidirectional communication between the gut and the brain. Although there has been much discussion in recent years on the link between depression and fecal microbiota transplantation (FMT), its effectiveness in treating depression remains debatable. The purpose of this study was to examine if FMT alleviates depression or its symptoms and to examine the possible impacts of various demographic subgroups and supplementation techniques.MethodsA systematic search of articles in the database (PubMed, EMBASE, Web of Science, and Cochrane libraries) before March 2025. The Revman 5.3 software was used to incorporate standardized mean difference (SMD) and assess quality of evidence using recommended grading assessment, development and evaluation tools to investigate whether FMT efficacy on depressive symptoms or depression.ResultsThis meta-analysis included seven studies involving 235 subjects, and the results did not support a significant treatment effect of FMT on depression [SMD: -0.10; 95%CI: (-0.60,0.41); p = 0.71]. Subgroup analysis showed the correlation between the intervention effect of FMT and confirmed depression at baseline, intervention dose, donor source, repeated route of drug administration, and dietary habits of subjects.ConclusionsThere is insufficient evidence to support a significant efficacy of FMT on depressive symptoms, but subgroup analyses suggest that FMT may have a better antidepressant effect in the population with confirmed depression, and therefore more randomized controlled trials are necessary to validate the association between FMT and depressive symptoms.